Ulysses in progress - Groden, Michael (Princeton legacy library, 1977)
The publication of James Joyce's Ulysses crowned years of writing and constant rewriting at almost every stage, so that as many as ten versions exist for some pages. To understand how Joyce worked, Michael Groden traces the book's history in detail, synthesizing evidence from notebooks, drafts, manuscripts, typescripts, and proofs. Originally published in 1977. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.